Intangible spirits and graven images : the iconography of deities in the pre-Islamic Iranian world - Shenkar, Michael. (Magical and Religious Literature of Late Antiquity, 2014)
Winner of the the Roman and Tania Ghirshman Prize 2015 by the French Académie des Inscriptions et Belles-Lettres. This prize was established in 1973 by the donation made by Roman Ghirshman, one of the prominent French archaeologists of Pre-Islamic Iran. It is awarded annually for a publication in the field of Pre-Islamic Iranian Studies. In Intangible Spirits and Graven Images , Michael Shenkar investigates the perception of ancient Iranian deities and their representation in the Iranian cults. This ground-breaking study traces the evolution of the images of these deities, analyses the origin of their iconography, and evaluates their significance. Shenkar also explores the perception of anthropomorphism and aniconism in ancient Iranian religious imagery, with reference to the material evidence and the written sources, and reassesses the value of the Avestan and Middle Persian texts that are traditionally employed to illuminate Iranian religious imagery. In doing so, this book provides important new insights into the religion and culture of ancient Iran prior to the Islamic conquest.